2005
DOI: 10.1175/mwr-2840.1
|View full text |Cite
|
Sign up to set email alerts
|

Spectral (Bin) Microphysics Coupled with a Mesoscale Model (MM5). Part I: Model Description and First Results

Abstract: Considerable research investments have been made to improve the accuracy of forecasting precipitation systems in cloud-resolving, mesoscale atmospheric models. Yet, despite a significant improvement in model grid resolution and a decrease in initial condition uncertainty, the accurate prediction of precipitation amount and distribution still remains a difficult problem. Now, the development of a fast version of spectral (bin) microphysics (SBM Fast) offers significant potential for improving the description of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
147
1
4

Year Published

2009
2009
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 140 publications
(159 citation statements)
references
References 78 publications
7
147
1
4
Order By: Relevance
“…Many studies have shown that aerosol effects on precipitation depend on the large-scale environment and cloud type (e.g. Khain et al, 2004;Fan et al, 2007;Lynn et al, 2005a, b;Lynn and Khain, 2007;Seifert and Beheng, 2006a;Tao et al, 2007) for reasons related to differences in different cloud types between the timescale of increased sedimentation through aerosol loading and subsequent sublimation and evaporation timescales. Further, several studies of deep convection have found that the effects of aerosol on deep convection are much weaker than those of relative humidity (e.g.…”
Section: Congo Supercell Ricomentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies have shown that aerosol effects on precipitation depend on the large-scale environment and cloud type (e.g. Khain et al, 2004;Fan et al, 2007;Lynn et al, 2005a, b;Lynn and Khain, 2007;Seifert and Beheng, 2006a;Tao et al, 2007) for reasons related to differences in different cloud types between the timescale of increased sedimentation through aerosol loading and subsequent sublimation and evaporation timescales. Further, several studies of deep convection have found that the effects of aerosol on deep convection are much weaker than those of relative humidity (e.g.…”
Section: Congo Supercell Ricomentioning
confidence: 99%
“…This can lead to significant differences in the cloud and precipitation simulated by bin vs. bulk schemes. For example, bulk schemes have been shown to underestimate areas of weak and stratiform rain in an MCS compared to a bin scheme which performed better against observations (Lynn et al, 2005a, b). Li et al (2009a, b) showed that a one-moment bulk scheme was shown to be worse at partitioning rain into stratiform and convective components in a continental squall line compared to a bin scheme (although many studies have shown that two-moment schemes are a significant improvement on single-moment schemes; e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Delayed autoconversion due to higher CDNC provides more abundant cloud liquid to be transported into unsaturated areas as the source of this increased evaporation. These feedbacks between dynamics and microphysics are described in more detail in Lee et al (2008a) and simulated in Khain et al (2003Khain et al ( , 2004Khain et al ( , 2005Khain et al ( , 2008 and Lynn et al (2005). Lee et al (2008b) indicated that increases in updrafts, leading to increases in condensation and deposition, were much larger in deep convective clouds than those in shallow clouds at high aerosol as shown in Fig.…”
Section: Microphysical Properties Of Cloudsmentioning
confidence: 78%
“…Ramanathan et al (1989) indicated that radiaitve properties of deep convective clouds were different from those of stratiform clouds, regarding the modulation of outgoing longwave radiation. Also, recent studies showed aerosols could change microphysical and dynamical properties of deep convective clouds (Khain et al, 2003(Khain et al, , 2004(Khain et al, , 2008Lynn et al, 2005;Tao et al, 2007;Lee et al, 2008a). Lee et al (2008b) found that aerosol effects on cloud mass and precipitation were different for deep convective and shallow stratiform clouds.…”
Section: Introductionmentioning
confidence: 99%
“…Recent and similar efforts to couple a bin microphysics scheme into MM5 and WRF were presented by Lynn et al (2005), Lynn et al (2007), Khain and Lynn (2009) and Khain et al (2010), who utilized the spectral microphysics scheme of the Hebrew University of Jerusalem (HUJI-SBM) into MM5 and later in WRF. One feature that makes the Xue et al (2010) scheme the most adequate to study mineral dust and cloud interaction is their development and coupling of an aerosol recycling mechanism that prevents the diminishing of aerosol particles from the domain due to cloud and rain drops evaporation.…”
mentioning
confidence: 99%